Inhalation human health risk assessment: case study of a South African international airport - Dubazana, Makhosazana (My University, 2020)
There has been an increase in public health concerns due to the impact of airport-related emissions on public and occupational health. Many studies have evaluated the potential health risk of a wide range of toxic pollutants within an airport. However, there has not been enough work done to analyse the potential human health impact of benzene, toluene, ethylbenzene, and xylene (BTEX), which occurs within airport environments in significant amounts. Besides, BTEX compounds are known to have a wide range of health impacts, where humans exposed to these compounds for an extended period or over their lifetime are known to develop symptoms such as wheezing and headaches, which are associated with the general effects of BTEX on the nervous system. Furthermore, benzene exposure is associated with the development of leukaemia. This study aimed to assess the human health risk of BTEX compounds on hypothetical subpopulations groups of residents living near a privately-owned South African airport chosen for this study as well as on-site employees. The study utilised the US EPA guidelines on Human Health Risk guide materials and methods. The results of the average ambient air emissions are 2.69, 7.43, 1.53, and 5.36 ug/m-3 for benzene, toluene, ethylbenzene, and xylene, respectively. The ambient emissions were higher during the winter sampling campaign, with total BTEX concentrations ranging from 13.93 to 44.36 ug/m-3. BTEX seasonal and spatial variations were evident: concentrations dispersed from the southwest (lowest concentrations) to the northeast (highest concentration) end in the autumn and winter. On the other hand, in spring and summer, there were emission hotspots on either side of the runway. The results of the final risk assessment displayed similar spatial distributions to benzene emission; the highest cancer risk is at the emissions hotspots at the airport drop-off area and parking. The cancer risk was above the US EPA guideline of 1 x 10-6 for all locations. The residential subpopulation groups have an average cancer risk of 6.44 x10-05, while on-site employees have an average cancer risk of 2.66 x 10-06. The results of the general health risk measured through the Hazard Quotient were below 1 for most subpopulation groups, excluding the subpopulation group younger than six months. With the prolific increase in air traffic transportation and the probable deterioration of air quality, the resultant associated health risk for populations in and around airports may intensify, which is a cause for concern and further investigation
A dissertation submitted to the Faculty of Science, in fulfilment of the Master of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2020
Keywords: Hazardous substances--Risk assessment; Environmental health